The inherent electrochemistry of nickel/nickel-oxide nanoparticles - Giovanni, Marcella (2013)
The direct detection of nanoparticles is at the forefront of research owing to their environmental and toxicological applications. Herein, we studied the inherent electrochemistry of Ni and NiO nanoparticles and proposed a simple and direct electrochemical method for the determination of the concentrations of both nickel (Ni) and nickel oxide (NiO) nanoparticles in alkaline solution. A highly sensitive voltammetry technique was used to measure the oxidative signal of Ni(OH)2 that formed spontaneously on the surface of Ni and NiO nanoparticles in alkaline media. Detection limits of 220 μg mL−1 for Ni and 13 μg mL−1 for NiO nanoparticles were obtained. Ni and NiO nanoparticles are used as electrode modifiers or as electrochemical signal labels in various biosensing applications. Therefore, methods to rapidly quantify the amount of Ni and NiO nanoparticles are of widespread potential use.